UTILIZATION OF DIGITALIZATION AND INNOVATION FOR THE DEVELOPMENT OF MSMES IN THE DIGITAL ERA - Diwayana Putri Nasution; Muetia Handayani; Cut Yunina Eriva; Devi Mulia Sari; Mislinawati; Mutia Arfiani; Ardian Ardian; Muhammad Abthahi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The purpose of this study is to investigate the role of digitalization and innovation in the growth and development of MSMEs. Digitalization is essential in the global era, where human resources are required to adapt to digitalization developments. Innovation is closely related to digitalization in its optimization. However, in reality, this has not yet occurred comprehensively in various aspects of MSMEs. The background to this research is the many MSMEs that still lack adequate capabilities in terms of digitalization and innovation. The research method employed is a literature review, examining previous studies that analyze the use of digitalization and innovation for the development of MSMEs. The results show that the use of digitalization and innovation has a significant influence on improving MSME development. Indicators and aspects of digitalization are also necessary for more optimal MSME development. The recommendations from this study are the need for collaboration, training, and digital literacy in innovation and digitalization as an effort to develop MSMEs that are globally competitive in the digital era.